Renewal of the Culture of Thinking and Philosophical Reflections - Norov Said (Zien Journals, 2022)
The article discusses the peculiarities of modern social development, the development of social consciousness and the deepening of humanity in the mysteries of the world, the renewal of the culture of thought and philosophical observation of the XXI century.
Keywords: man; philosophy; way of thinking; development